Knowledge of COVID-19 and the impact on indigents’ access to healthcare in Burkina Faso - Bonnet, Emmanuel; Beaugé, Yvonne; Ba, M. F.; Sidibé, S.; De Allegri, Manuela; Ridde, V. (International journal for equity in health, 2022)
COVID-19 constitutes a global health emergency of unprecedented proportions. Preventive measures, however, have run up against certain difficulties in low and middle-income countries. This is the case in socially and geographically marginalized communities, which are excluded from information about preventive measures. This study contains a dual objective, i) to assess knowledge of COVID-19 and the preventive measures associated with it concerning indigents in the villages of Diebougou’s district in Burkina Faso. The aim is to understand if determinants of this understanding exist, and ii) to describe how their pathways to healthcare changed from 2019 to 2020 during the COVID-19 pandemic.